Peru : Third Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2003)
Peru showed commendable economic performance under the Stand-By Arrangement, owing to its strong fundamentals, prudent macroeconomic policies, and progress with structural reforms. Executive Directors commended these developments, and stressed the need to strengthen fiscal prudence, transparency, debt management, and monetary policy stance. They emphasized the need to implement tax and pension plan reforms, and improve the public sector operations and banking sector indicators. They agreed that Peru has successfully completed the third review under the Stand-By Arrangement.